2021
DOI: 10.1017/sus.2021.20
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the food–energy–water nexus approach to enhance coastal community resilience research and planning

Abstract: Non-technical summary. Coastal communities face environmental challenges that put food, energy, and water systems at risk. Although highly interdependent, it is unknown the extent to which coastal resilience research has considered interactions among food-energy-water systems. Twenty peer-reviewed articles were identified that focused on these systems and coastal resilience. Although a nexus approach was not employed universally, these studies most commonly addressed interactions among these systems related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 93 publications
0
0
0
Order By: Relevance
“…In the first study, a systematic literature review of peerreviewed, academic literature was conducted. This revealed that, as of 2020, only twenty studies had combined the topics of the food-energy-water nexus with resilience (Raub et al, 2021a). In the second exploratory study, a document analysis was conducted to assess how the FEW nexus had been applied in the context of community resilience plans (Raub et al, 2021b).…”
Section: Flood Resilience and The Few Nexus: Planning And Policy Chal...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the first study, a systematic literature review of peerreviewed, academic literature was conducted. This revealed that, as of 2020, only twenty studies had combined the topics of the food-energy-water nexus with resilience (Raub et al, 2021a). In the second exploratory study, a document analysis was conducted to assess how the FEW nexus had been applied in the context of community resilience plans (Raub et al, 2021b).…”
Section: Flood Resilience and The Few Nexus: Planning And Policy Chal...mentioning
confidence: 99%
“…For instance, when an electrical substation is damaged as a result of a flooding event, it affects the water, telecommunications, and other systems that are connected to that substation. The literature review also found that while the foodenergy-water nexus can usefully provide a starting point, other systems such as transportation should be added to the nexus, as needed (Raub et al, 2021a). Findings from the analysis of publicly available resilience plans suggested that, while reference to the FEW nexus was not explicit, there was evidence that a broader nexus approach was increasingly recognized as being relevant to resilience planning (Raub et al, 2021b).…”
Section: Flood Resilience and The Few Nexus: Planning And Policy Chal...mentioning
confidence: 99%
“…If approached with caution, urban resilience planning offers flexibility to incorporate many different contributors, disciplines and their interactions. 34 Furthermore, urban resilience is highly dependent on the interconnectedness of the urban systems—most notably energy and transportation—with long-term effects felt most acutely in the water system 3 , 35 making the Nexus an obvious additional layer in the urban resilience planning fabric.…”
Section: Introductionmentioning
confidence: 99%
“…A resilience operation method for the formation of several MGs after a natural disaster in the distribution network has been studied in [12], and after the maximum critical load was retrieved by distributed generation sources following the accident, this reference only investigated the effect of distributed generation resources and MG formation on improving resilience and, in the case of natural disasters, on electricity and gas infrastructures. Other forms of energy such as heat, water, etc., are not mentioned, although in the event of natural disasters such as storms, damage to all infrastructures is possible [13]. Such events could result in the outage of important distribution network equipment and cause irreversible damage to the electrical network and must be addressed.…”
Section: Introductionmentioning
confidence: 99%